Enhancement of impact toughness properties of Al 7075 alloy via double aging heat treatment - Onur ALTUNTAŞ (Gazi Üniversitesi Fen Bilimleri Dergisi, 2022)
In this study, Charpy impact test specimens were prepared by cutting Al 7075 alloy according to ASTM-E23 standards. The prepared test specimens were dissolved in a single-phase region for 1 hour at 480°C in vacuum atmosphere and artificially aged at 120°C for 24 hours after quenching. After the first step aging heat treatment applied, the specimens were artificially aged for 5-50 hours at 180°C for the second time. Microstructural characterization and fracture surface analyzes of the specimens were determined using SEM (Scanning Electron Microscope) device, crystallographic analysis of the precipitated phases were determined using XRD (X-ray diffraction) device. The increase in the amount of ƞı phase (MgZn2) with increasing double aging heat treatment time was effective in increasing the strength. After 10 hours of double aging heat treatment, the impact toughness value is improved by 300% compared to the single aged condition.